WATER SUSTAINABILITY: RECOVER, RECYCLE AND REUSE - State Planning Board, Government of Kerala
Water is a precious resource and it has to be treated as such. Water and sanitation go hand in hand. The challenge in Kerala is mainly the management of water and waste management. The strategy should be one of sustainable integrated management of water in all areas. Water needs to be conserved and valued. Recovering, recycling and re-using of water is the sustainable way out. New technologies will be adopted both on the supply and demand side for using water in a conservative fashion. Pricing and water metering may be used to monitor water usage. Micro irrigation schemes are recommended for Kerala. Plus water availability 24*7 is a key hallmark of smart, compact and global cities. Existing rural water schemes may be extended to supply water in the rural areas. Scaling up of infrastructure would be expensive and may be financed through financing from the Diaspora.